Distributed control plane for safe cooperative vehicular cyber physical systems. Issue 1 (27th November 2019) - Foukalas, Fotis; Pop, Paul
Abstract : Cooperative vehicular cyber physical systems build a group of entities that can accomplish a cooperative task using the distributed control approaches. To this end, such a cooperative task can be coordinated and managed by a distributed control plane that will be able to encapsulate all the required functionality in a layered architecture providing the required interoperability. Here, the authors propose such a distributed control plane that consists of the cooperative awareness layer, the communication layer and the distributed control layer. Wireless communications play an important role for the mobility provision, taking into account different constraints in order to provide high reliability and low latency. A simulation environment is considered with a leader–follower control format, where the reliability is evaluated. Further, a distributed safety monitoring approach is devised, given a control diagram and mapping of the events to the different components. The event monitoring relies on the self‐triggered approach, where a use case is evaluated to highlight the impact of the input and output delays to the model predictive control component of the overall distributed control diagram including the calculation of the number of triggered events.